Self as a Cluster of Socio-cultural Simulacra: Georg Simmel and Luigi Pirandello's Feminist Anthropology of Acting - Čale Feldman, Lada (Array, 2000)
The paper emphasizes one common aspect of both Simmel's and Pirandello's alleged postmodernity: the connection of their feminism with their strikingly similar, socio-culturally grounded theories of acting/living, namely existing/performing and thus (womanly) overcoming the painful dualisms tearing the (men's) culture apart: mind and body, emotion and cognition, art and life, actors and onlookers, subject and object, self and its other, within and without.